Density and Relativity Abundance of the Prawn and Shrimps in Al-Hammar and Al-Chibayish Marshes of Southern Iraq - Jodha, Rawan D.; Hamza, Haifa A. (Iraqi Journal of Aquaculture, 2023)
The current study was conducted to calculate the annual Occurrence, monthly density and relative abundance of the Metapenaeus affinis. The samples were collected monthly for the period from October 2017 to September 2018. Some environmental factors such as temperature of water and air, pH, salinity, dissolved oxygen and turbidity were measured. We obtained 7 types of shrimp belonging to three families in the Al-Burka station and the Al Sabbaghia Station , which are 7 species, all of which belong to the Division of arthropods and crustaceans, the first family: Penaeidae is a banyan family that includes Metapeneaus affinis, Penaeus semisulcatus, Family: Atyidae, include Caridina babaulti basrensis , Atyaephyra desmaresti mesopotamica and Family: Palamonidae includes Exopalaemon styliferus, Palaemon elegans and Macrobrachium nipponense divided into four categories according to the Yearly Occurrence Resident, Fluctuated, Occasional, Rare. The monthly density of each species of shrimp was calculated and the range was: for Metapenaeus affinis 0-325.85 Ind./ m² and Penaeus semisulacatus 0-5.32 Ind./ m² and Caridina babaulti basrensis 0-111.72 Ind./ m² Atyaephyra desmaresti mesopotamica 0-679.63 Ind./ m² Exopalaemon styliferus 0-23.94 Ind./ m² Palaemon elegans 0-19.95 Ind./m² Macrobrachium nipponense 0-55.86 Ind./ m². The highest density in the Al-Burka station for Metapeneaus affinis to 2600.15 Ind./ m² The Lowest density for Penaeus semisulacatus to 9.31 Ind./ m² and the highest density in the Al Sabbaghia Station for cardinia babaulti basrensis to 320.53 Ind./ m² and the lowest density for Exopalaemon styliferu at 3.99 Ind./ m² and The total density of the Al-Burka station in the east Al-Hammar Marsh was higher than the. Al Sabbaghia Station In Chabaish Marsh. The monthly abundance of shrimp was calculated as Metapenaeus affinis 0-100%, Penaeus semisulacatus 0-1.87 %, Caridina babaulti basrensis 0-93.33 %, Atyaephyra desmaresti mesopotamica 0-100 %, Exopalaemon styliferus 0-27.27% ,Palaemon elegans 0- 26.66 % , Macrobrachium nipponense 0-73.33 %. The results of the statistical analysis showed a positive relationship between abundance and water temperature, pH and salinity and showed significant differences between abundance and acuityP< 0.007 between sovereignty and mean P< 0.018 The correlation coefficient was positive between abundance and (temperature water, pH , Salinity and acacia) and the correlation coefficient between abundance and dissolved oxygen.